PENGARUH PENDEKATAN PMRI TERHADAP KEMAMPUAN PENALARAN MATEMATIS DAN SELF-ESTEEM SISWA DI SD - Rachel Angelina Putri; Nila Kesumawati; Putri Dewi Nurhasanah (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The low level of mathematical ability in learning is important to note. Therefore, improving mathematics ability through self-esteem is needed using the PMRI approach. One of the personality factors that influences student learning outcomes is self-esteem. The method used in this research is the experimental method with quasi-experiments emu, which is Posttest Only Control Design. The research is carried out in three stages: planning, implementation, and evaluation. Based on the data analysis results, the conclusion was That the PMRI approach influences the ability of mathematical reasoning and self-esteem of students of grade V SD Negeri 143 Palembang. There is a correlation between the ability to reason mathematically and the self-esteem of students of class VSD Negeri 143.